TINGKAT ADOPSI PETERNAK DALAM PENERAPAN INOVASI AYAM KAMPUNG UNGGUL BALITBANGTAN (KUB) DI KABUPATEN KAMPAR - Reni Astarina; Rosnita Rosnita; Yeni Kusumawaty (Fakultas Pertanian, Universitas Riau, 2020)
This study aimed to determine the adoption of breeders to the innovative Balitbangtan (KUB) native chicken in Kampar Regency and the level of adoption of breeders in adopting the KUB chicken innovation. This research was conducted to evaluate the program of the Riau Agricultural Technology Research Institute (BPTP), which is where the author works. The research lasted for one year, from July 2019 to July 2020. The research sample was taken by means of a census, namely all breeders who cultivated KUB chickens, totaling 50 breeders in Kampar Regency, were the samples in this study. The results showed that; The adoption rate of KUB Chicken breeders was low where most breeders chose not to continue to implement or adopt the KUB Chicken business and the KUB Chicken innovation characteristic factors had a very weak correlation or significance relationship to the KUB Chicken innovation adoption rate in Kampar Regency.